Parents helping their children learn to read: The effectiveness of paired reading and hearing reading in a developing country context. (December 2013) - Shah-Wundenberg, Mihika; Wyse, Dominic; Chaplain, Roland
This paper reports research that investigated parental support for children's reading of English in an inner-city school in the developing country context of an Indian city, Ahmedabad. Children had oral proficiency in the regional language but were beginning to acquire conventional forms of literacy in English. Sociocultural mediation theory underpinned a mixed-methods research design. A quasi-experimental trial with a sample of 241 children was conducted to assess the relative effectiveness of two approaches to parents supporting reading: Paired Reading and Hearing Reading. Interviews and observations with a smaller sub-sample of parents and children were utilised to further explore the implications of the trial data. Paired Reading and Hearing Reading were found to be equally effective in enhancing children's beginning English reading skills, reading accuracy and comprehension, relative to controls. Parents engaged in a variety of mediation behaviours to enhance their children's English reading development. Parents felt that participating in their children's reading was both enriching and empowering. In view of the evidence that Hearing Reading can be, and was, implemented by parents with little or no English language proficiency, it is concluded that implementing Hearing Reading on a wider scale across the city could impact beneficially on children's English reading development.